English Oral Presentation Skills among DAD1 Students of Politeknik Sultan Mizan Zainal Abidin - Farina Ayu Binti Mahmud; Norsaliza Binti Osman (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2023)
This action research is aimed to overcome students’ difficulties in delivering good English oral presentation. This research involves 40 semester one Diploma in Mechanical Engineering (Automotive) students of Politeknik Sultan Mizan Zainal Abidin (PSMZA) June 2017 session. The objectives of this research are to find out the oral presentation skills of DAD1-S1 students, to identify the factors that lead to ineffective English oral presentation skills and to find out students interest in preparing effective English oral presentation skills. The methodologies used in this research are combination of quantitative and qualitative. The data were gathered through questionnaires and also from observation and was analyzed using graphs and tables. Based on data gathered, it was found that 62% of students have limited ability to deliver good oral presentation. Therefore, three action plans have been implemented within 10 weeks in order to help students to excel in oral presentation. The action plans carried out were videos viewing, topic of interest presentation and phonetic learning .Based on the action plans conducted, 63% of DAD1-S1 students showed positive improvement in oral presentation in final observation. Confident level was found as the main factor lead to ineffective oral presentation of the students. 55% students claimed they have interest in preparing and delivering good presentation. The results of the actions implemented verified that students’ oral presentation skills can be improved if they are given sufficient exposure and practices.